Going belowground: burying anthropomorphic biases on gustation and olfaction - Elmquist, Dane C.; Eigenbrode, Sanford D. (Frontiers in Ecology and Evolution, 2023)
Chemical signaling underpins behavioral interactions among organisms in the soil. Understanding chemical communication in the soil requires a paradigm shift in methodology and perspectives compared to aboveground ecosystems because olfaction and gustation, accepted modalities of chemosensation aboveground, may not accurately represent chemical communication in the soil. To fully understand chemical communication in the soil, it is essential to consider how soil properties, such as moisture, pH, and adsorption, affect the transport and perception of semiochemicals. De-anthropomorphizing the study of chemosensation can avoid potential biases, particularly in soil systems, where distinctions between olfaction and gustation are confounded by the heterogeneity of the soil environment and its effects on the mobility of chemical signals. In this perspective, we first explore how soil heterogeneity confounds the dichotomy between olfaction and gustation with hypothetical but ecologically relevant examples. Then we examine how anthropomorphic biases in aboveground chemical ecology have influenced soil chemical ecology. Our examples and discussion are prepared primarily in reference to soil arthropods. We conclude by discussing seven future research directions and outstanding questions. The soil is a premier example of a system where investigators should avoid anthropomorphisms when studying behavioral and chemical ecology. Research in soil chemical ecology should further efforts towards developing a unified view of chemosensation that could apply to all environments where chemical communication occurs.